"Words matter." A Response to Jørgensen's Treatment of Historic Range and Definitions of Reintroduction. Issue 2 (7th January 2013) - Dalrymple, Sarah E.; Moehrenschlager, Axel
Abstract According to Jørgensen, the definition of reintroductions is crucial to their proper implementation and she highlights a number of ambiguities in existing definitions, particularly associated with the concept of historic range. We could not agree more and have incorporated her suggested term of "indigenous range" rather than "historic range" into the current revision of the InternationalUnion for the Conservation of Nature (IUCN) Guidelines for Reintroductions and other Conservation Translocations (in preparation by IUCN Species Survival Commission Reintroduction and Invasive Species Specialist Groups). We also agree with Jørgensen's interpretation that reintroductions are not always necessitated by humans causing the extirpation of species. However, we disagree with other aspects of Jørgensen's argument such as the critique of Seddon, the interpretation of previous IUCN guidance documents, and the recommendation that the conservation community "rethink the basic definition of reintroduction" rather than moving toward other translocation‐based interventions. With regard to the latter point, we emphasize that reintroductions are part of a spectrum of translocations and to focus on reintroductions alone would overlook the fact that introductions beyond a species' indigenous range are being attempted. The new revision of the IUCN guidelines incorporates the whole conservation translocation spectrum and aims to avoid the ambiguities of previous definitions highlighted by Jørgensen.